2016
DOI: 10.1158/0008-5472.can-16-0438
|View full text |Cite
|
Sign up to set email alerts
|

IGFBP2 Activates the NF-κB Pathway to Drive Epithelial–Mesenchymal Transition and Invasive Character in Pancreatic Ductal Adenocarcinoma

Abstract: The molecular basis underlying the particularly aggressive nature of pancreatic ductal adenocarcinoma (PDAC) still remains unclear. Here we report evidence that the insulin-like growth factor-binding protein IGFBP2 acts as a potent oncogene to drive its extremely malignant character. We found that elevated IGFBP2 expression in primary tumors was associated with lymph node metastasis and shorter survival in PDAC patients. Enforced expression of IGFBP2 promoted invasion and metastasis of PDAC cells in vitro and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
82
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 92 publications
(84 citation statements)
references
References 45 publications
2
82
0
Order By: Relevance
“…Our results showed that IGFBP-2 was significantly upregulated in MCF10A.NeuT (C3 cells). IGFBP-2 has previously been reported to drive EMT and invasiveness in pancreatic ductal adenocarcinoma through activating the NF-κB pathway [33]. Consistent with this, NF-κB pathway receptors and downstream effectors, i.e.…”
Section: Discussionsupporting
confidence: 57%
“…Our results showed that IGFBP-2 was significantly upregulated in MCF10A.NeuT (C3 cells). IGFBP-2 has previously been reported to drive EMT and invasiveness in pancreatic ductal adenocarcinoma through activating the NF-κB pathway [33]. Consistent with this, NF-κB pathway receptors and downstream effectors, i.e.…”
Section: Discussionsupporting
confidence: 57%
“…Previous studies have suggested that NF-κB plays an essential role in the induction and maintenance of EMT (19,20). We proposed that the role of AREG-induced pancreatic cancer cell migration, invasion and EMT may be through regulation of the NF-κB signalling pathway.…”
Section: Inhibition Of the Nf-κb Signalling Pathway Suppresses Areg-imentioning
confidence: 89%
“…Many previous studies indicate that IGFBPs can promote tumor growth but can also function as anti-oncogenes [17]. IGFBP2 has been demonstrated to show promoted tumorigenicity in various cancer types [1,23,24]. And in high quality glioma studies, IGFBP-2 showed non conflicting results in predictive biomarkers [25].…”
Section: Discussionmentioning
confidence: 99%